Enhanced Light Emission from Type-II Red InGaN/GaNSb/GaN Quantum-Well Structures - Seoung-Hwan Park; Jong-In Shim; Dong-Soo Shin (Advances in Condensed Matter Physics)
Electronic and optical properties of type-II InGaN/GaNSb/GaN quantum-well (QW) structures are investigated by using the multiband effective mass theory for potential applications in red light-emitting diodes. The heavy-hole effective mass around the topmost valence band is not affected much by the insertion of the GaNSb layer, and the optical matrix elements are greatly increased by the inclusion of the GaNSb layer in the InGaN/GaN QW structure. As a result, the type-II InGaN/GaNSb/GaN QW structure shows a much larger emission peak than the conventional type-I QW structure owing to the decrease in spatial separation between electron and hole wavefunctions, in addition to the reduction of the effective well width. It is also observed that the In content in InGaN well can be significantly reduced for the type-II QW structure with a large Sb content, compared to that for the type-I QW structure.